From Leguminosae/Gramineae Intercropping Systems to See Benefits of Intercropping on Iron Nutrition - Dai, Jing; Qiu, Wei; Wang, Nanqi; Wang, Tianqi; Nakanishi, Hiromi; Zuo, Yuanmei (Frontiers in Plant Science, 2019)
To achieve sustainable development with a growing population while sustaining natural resources, a sustainable intensification of agriculture is necessary. Intercropping is useful for low-input/resource-limited agricultural systems. Iron (Fe) deficiency is a worldwide agricultural problem owing to the low solubility and bioavailability of Fe in alkaline and calcareous soils. Here, we summarize the effects of intercropping systems on Fe nutrition. Several cases showed that intercropping with graminaceous plants could be used to correct Fe nutrition of Leguminosae such as peanut and soybean or fruits such as Psidium guajava L., Citrus, grape and pear in calcareous soils. Intercropping systems have strong positive effects on the physicochemical and biochemical characteristics of soil and the microbial community due to interspecific differences and interactions in the rhizosphere. Rhizosphere interactions can increase the bioavailability of Fe with the help of phytosiderophores. Enriched microorganisms may also facilitate the Fe nutrition of crops. A peanut/maize intercropping system could help us understand the dynamics in rhizosphere and molecular mechanism. However, the role of microbiome in regulating Fe acquisition of root and the mechanisms underlying these phenomena in other intercropping system except peanut/maize need further work, which will help better utilize intercropping to increase the efficiency of Fe foraging.